An energy saving smart pedestrian lighting system with IoT - Gheni, Hasan Muwafaq (2019)
A large quantity of electricity in many countries is consumed towards lighting up the streets. Most of the basic street lighting systems are switched ON/OFF at regular intervals of time. In this thesis, a system is proposed to develop an energy saving pedestrian light control system to reduce energy consumption. This is done by having an automatic system that detects human presence near the pedestrian path. Consequently, this system may save a large amount of electrical power as well as increase the lamp's lifetime and reduce pollution. The system works by keeping lamps on an off state at all night, except a few which will serve as guide lamps. When someone approaching the pedestrian path, an IR sensor sends a message to a microcontroller to turn the lamps ON. An Arduino microcontroller has been used as a controller for the project in addition to other components used for this system such as IR sensor, a current sensor, LDR sensor, RF wireless module, and ESP8266 module. In order to monitor the system at anytime and anywhere, the system is connected to the IoT cloud via Thingsboard using a WiFi network connection. The proposed system has been observed to reduce power consumption by 40-45 percent compared to conventional system.